Direct laser writing for cardiac tissue engineering: a microfluidic heart on a chip with integrated transducers. Issue 9 (22nd March 2021) - Jayne, Rachael K.; Karakan, M. Çağatay; Zhang, Kehan; Pierce, Noelle; Michas, Christos; Bishop, David J.; Chen, Christopher S.; Ekinci, Kamil L.; White, Alice E.
Abstract : We developed an organ-on-a-chip platform with integrated stimulators and sensors. The platform is fabricated using direct laser writing (DLW) and allows for generation and study of functional 3D cardiac microtissues in controlled microenvironments. Abstract : We have developed a microfluidic platform for engineering cardiac microtissues in highly-controlled microenvironments. The platform is fabricated using direct laser writing (DLW) lithography and soft lithography, and contains four separate devices. Each individual device houses a cardiac microtissue and is equipped with an integrated strain actuator and a force sensor. Application of external pressure waves to the platform results in controllable time-dependent forces on the microtissues. Conversely, oscillatory forces generated by the microtissues are transduced into measurable electrical outputs. We demonstrate the capabilities of this platform by studying the response of cardiac microtissues derived from human induced pluripotent stem cells (hiPSC) under prescribed mechanical loading and pacing. This platform will be used for fundamental studies and drug screening on cardiac microtissues.